Tradução e adaptação cultural do “novel modification of the reported edmonton frail scale” (mod-refs) para o contexto brasileiro - Dias, Ana Laura Oliveira (Universidade Federal de São Carlos, 2021)
Frailty emerges as a significant concept, with the challenge of facilitating its recognition in the current health system. Although it is a progressive condition, frailty can be prevented, monitored and rehabilitated. Instruments designed to identify frail elderly people living in the community, allow early intervention and management of risk factors, enabling the maintenance of quality of life with a guarantee of the individual's autonomy and independence. In view of this, a group of Australian researchers has adapted the Reported Edmonton Frail Scale to a new version, entitled, Novel modification of the Reported Edmonton Frail Scale (mod-REFS), which aims to track frailty in hospitalized elderly. Based on the above, the objective of this methodological study is to carry out the translation and cultural adaptation of the Novel Modification of the Reported Edmonton Frail Scale (mod-REFS) into Brazilian Portuguese. The translation and cultural adaptation process included the steps of initial translation, synthesis of translations, back-translation, review by a committee of judges and pre-test, which is still in progress. The instruments used for the pre-test were: Characterization Questionnaire, [10-Point Cognitive Screener (10-CS), pre-final version of the Novel Modification of the Reported Edmonton Frail instrument and the General Impression Instrument for semantic validation adapted from Disabkids . The instrument showed good levels of internal consistency, indicating good quality of this version, being eligible for comparison with versions from other countries. The present study hopes to make available the adapted version of the Novel Modification of the Reported Edmonton Frail Scale for the Brazilian context and that, in the future, after the process of analyzing the psychometric properties of the instrument, it will make normative data available to the local population. available for assistance in order to facilitate the assessment, intervention and prevention of hospitalized elderly people facing the frailty syndrome.
Translation and adaptation of the “novel modification of the reported edmonton frail scale” (mod-refs) for the brazilian context
Keywords: Tradução; Estudos transculturais; Idoso fragilizado; Fragilidade; Hospitalização; Brasil; Cross-cultural study; Frail elderly; Fragility; Hospitalization; Brazil; CIENCIAS DA SAUDE